Sanktuarium Asklepiosa w Epidauros - Przybyłek, Monika (Collectanea Philologica, 2011)
The article brings up the topic of ancient sanctuary of Asclepius in Epidauros, the biggest health centre in ancient Greece. However, enclosing its function to religious and health centre would be huge misunderstanding. Asklepieion was real centre of social and political life. The article discusses multipurpose of sanctuary by analysis of function of the most important buildings in the complex. Furthermore, in sanctuary, there were used contemporary methods of medicine: minor operations, hydrotherapy and treatment by art. Additionally, the theatre could take special place in process of healing. In Conclusion, the worship of Asclepius wasn’t eliminate development of science, but contrarily, both of its aspects coexisted together.